Hospital designs in tropical Malaysia: towards a green agenda - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Aripin, Srazali (2013)
‘Sustainability’ as a terminology, is a broad concept with a tendency of being abused through being trendy and over commercialisation. In the arena of hospital design, new is always associated to being modern. Modern hospitals now must be green or designed with sustainability concept. In the quest of getting to know the “tree” from “the forest” from among the hundreds of existing hospitals ranged from colonial, early independence to new hospital designs, a yardstick to measure those that is actually “green” and “sustainable” need to be set. The study intend to provide definition and criteria of green hospital designs in local tropical Malaysia apart from global definition. A qualitative methodology through case studies of hospital designs throughout the century was adopted for the study to look into aspects of the architecture that significantly affect health through effect of building configuration, form, space quality and material use. Preliminary findings indicate that there are both intuitive and mandatory green considerations in the designs, but had however over times overcome by quantum of the development that require compromises through prioritization due many factors from among others, condition of the site, construction, planning and economics. Significance of the findings will contribute to the criteria for healthcare building Green requirement in tropical Malaysia.